Mezzittia Becc (Annonaceae) : a New Generic Record for India from Andamans - Mathew, Sam P.; Mitra, Debika (Indian Forester, 1991)
Mezzettia cartisii King (Annonaceae)-a new generic record for India from Mt. Harriet hill ranges (South Andaman) is described with an illustration.